Effect of Pruning on Cocoa (Theobroma cacao L.) Growth Performance and Cocoa Disease Incidence - Olga Ingan, Anak Matheus Gires (Universiti Malaysia Sarawak (UNIMAS), 2017)
This research was conducted at Cocoa Research and Development Centre, Malaysian Cocoa Board, Kota Samarahan, Kuching Sarawak. The objective of this research was to determine the most suitable level of pruning for cocoa plant based on sunlight penetration and to observe the connection between different levels of pruning and presence of disease which in this case is the black pod and VSD disease. Three plots were used in this study which was plot A, B and C. Plot A is the plot with 25% level of pruning whereas plot B has 50% level of pruning and plot C has 75% level of pruning. The method used is by randomly choosing 20 trees from each plot with a zigzag design. In each plot, the total cocoa pods and also pods infected with black pod disease was counted in order to calculate and observe the difference in percentage of infection between the three plots. The leaves of the 20 trees chosen in each plot were also observed for vascular-streak dieback (VSD) disease based on the severity scale. The soil pH for the three plots was taken by using a portable WalkLAB HP9000 pH meter. The light intensity for the three plots was measured by using Extech LT300 light meter. Twenty spots were chosen in each plot to measure the light intensity and soil pH and the readings were taken fortnightly. The result of soil pH shows that plot C (75%) has a slightly acidic soil compared to plot B (50%) and plot A (25%). The overall result obtained showed that plot C (75%) which has the highest amount of light penetration shows a lower percentage of infection of black pod and VSD disease compared to plot B (50%) and plot A (25%). Plot A (25%) shows the opposite result compared to plot 75% where it has the highest percentage of infection for both black pod and VSD disease. Therefore, it can be concluded that pruning is one of the methods that can be used to control outbreak of disease in cocoa farms.